2021
DOI: 10.1108/yc-08-2021-1374
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Millennial behaviour towards current and future use of video streaming services

Abstract: Purpose This study aims to investigate the evolution of factors that influence the current and future use of video streaming applications by Millennial consumers. Design/methodology/approach Combining technology acceptance, perceived values and user identity theory this study used factor analysis and multiple regression to examine data from a survey of 292 university undergraduates. Findings Millennial’s current and future use of video streaming services remains driven more by social and emotional values a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Another factor, PVC, was also a significant factor influencing the OTT consumption behavior of youths in earlier studies (Sadana and Sharma, 2021). Previous studies revealed that ease of use, convenience, and monetary value have less influence among millennial consumers of OTT (Walsh & Singh, 2021). But, our research proves that all these factors are significant factors that influence customer satisfaction among Gen Z consumers.…”
Section: Discussionsupporting
confidence: 47%
“…Another factor, PVC, was also a significant factor influencing the OTT consumption behavior of youths in earlier studies (Sadana and Sharma, 2021). Previous studies revealed that ease of use, convenience, and monetary value have less influence among millennial consumers of OTT (Walsh & Singh, 2021). But, our research proves that all these factors are significant factors that influence customer satisfaction among Gen Z consumers.…”
Section: Discussionsupporting
confidence: 47%
“…First, the MGB combines emotional, habitual and motivational processes with the theory of planned behaviour's original components, providing more predictive power to behaviour than existing attitude-behaviour models (Singh and Sharma, 2022). Second, MGB considers anticipated emotions, enabling analysis of user motivation to use OTT streaming and encouraging a positive mindset whilst preventing a negative one during the streaming experience (Le and Wang, 2020); existing social-psychological models may not recognise this significant component (Walsh and Singh, 2022). Third, OTT users allocate time, resources and conscious effort to their OTT content consumption (Sahu et al, 2022), and viewers are expected to be motivated by specific goals.…”
Section: Theoretical Foundation 21 Integrating Mgb and Risk Theory In...mentioning
confidence: 99%
“…Our research aims to bridge this evident theoretical gap, which emerges from the evolving consumer preferences transitioning from traditional television viewing to OTT streaming platforms. Whilst preceding research on OTT adoption has enlisted various theories, such as niche theory (Sahu et al, 2021), uses and gratification theory (Menon, 2022), the theory of reasoned action (Nigam, 2022), perceived value theory (Walsh and Singh, 2022) and the unified theory of acceptance and use of technology (UTAUT) model (Bhattacharyya et al, 2022), the primary focus remains skewed towards the cognitive dimensions underpinning user behaviour .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also used other variables like the ease of use (Camilleri and Falzon, 2020;Walsh and Singh, 2021) and fear of missing out (Ajith and P, 2023), but none consider either attitude, flow, or habit an antecedent of continuance intention. In a meta-analysis of quantitative works from 2001 to 2017, which targeted the continuance intention of various information systems, Franque et al (2020) studied 115 articles published in multiple peer-reviewed journals.…”
Section: Theoretical Implicationsmentioning
confidence: 99%